Analisis Pengaruh PDRB, Angkatan Kerja, dan Upah Minimum Terhadap Penyerapan Tenaga Kerja di Provinsi Kalimantan Selatan Tahun 2010-2022 - Christy, Aurelia Natalie; Fahrati, Eny (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2024)
This study was conducted to determine the impact of GRDP, Labor Force, and Provincial Minimum Wage variables on Labor Absorption in South Kalimantan Province in 2010-2022. Time series data regression analysis was chosen as the method  and processed using Eviews 12 software.. The results of data processing show that the variables of GRDP, Labor Force, and Provincial Minimum Wage together have a significant effect on labor absorption in South Kalimantan Province. Meanwhile, Partially GRDP is detected to have a positive and insignificant effect on labor absorption in South Kalimantan Province, the Labor Force variable has a positive and significant effect on labor absorption in South Kalimantan Province. Then, the Minimum Wage variable has a negative and insignificant effect on labor absorption in South Kalimantan.